Effectiveness and challenges of problem-based learning implemented in engineering mathematics courses - Haliza Othman,; Noorhelyna Razali,; Nuryazmin Ahmat Zainuri,; Nur Arzilah Ismail,; Firdaus Mohd Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Presently, graduates of institutions of higher learning are found to be passive and not competent in carrying out the tasks assigned to them. The number of graduates that fail in a job interview has increased. One of the contributing factors is their ineffective communication skill during the interview, thus failing to exhibit their generic skills abilities in convincing the potential employer. As a proactive move to improve this issue, an initiative was carried out by the Faculty of Engineering and Built Environment (FKAB), Universiti Kebangsaan Malaysia (UKM) to introduce and implement problem-based learning (PBL) activities in the engineering mathematics courses. With the PBL method implemented at the early stage of the study period, the student’s ineffective communication issue can be addressed effectively. It is anticipated that the deployment of the PBL method can generally improve students’ soft skills, especially communication ability in meeting the demand and expectations of industry employers. The objectives of this study are to evaluate the effectiveness of the PBL implementation, thus identifying the benefits and the challenges of the PBL 5 Ladders of Active Learning strategy. In this study, the PBL activity was implemented in the Engineering Mathematics III (Differential Equation) course. To analyse the students’ feedback toward the implementation of the Five Ladders of Active Learning strategy and Self-Directed Learning method, the Rasch Measurement Model application software called Winstep was used. The results showed that the challenges faced during the PBL implementation are the readiness of lecturers as facilitators, the acceptance, and the readiness of students towards the learning process of the 5 Ladders of Active Learning strategy, the conducive learning environment, the crafting and constructing of PBL problems/triggers, the students’ reflection, and the PBL evaluation methods. To ensure that engineering students can master mathematics and generic skills as intended in the program, these challenges must be tackled effectively.